The paradox of water pricing: dichotomies, dilemmas, and decisions. (6th January 2020) - Grafton, R Quentin; Chu, Long; Wyrwoll, Paul
Abstract: We deliver a public policy perspective on the dichotomies, dilemmas, and decisions of water pricing. First, the dichotomies between price and value, and costs, are defined to explain the paradox of water pricing: the price of water almost never equals its value and rarely covers its cost. Second, the dilemmas of water pricing are highlighted across efficiency and equity, objectives for water pricing, and the instruments available to decision-makers. Third, the challenges of decision-making are evaluated and illustrated in relation to water pricing. Fourth, an adaptive process is provided that includes participatory assessment of risks and options to guide water-pricing decision-making.